Α-Synuclein Interactions in Mitochondria-ER Contacts: A Possible Role in Parkinson's Disease. (August 2022) - Erustes, Adolfo Garcia; Guarache, Gabriel Cicolin; Guedes, Erika da Cruz; Leão, Anderson Henrique França Figueredo; Pereira, Gustavo José da Silva; Smaili, Soraya Soubhi
Endoplasmic reticulum-mitochondria contact sites regulate various biological processes, such as mitochondrial dynamics, calcium homeostasis, autophagy and lipid metabolism. Notably, dysfunctions in these contact sites are closely related to neurodegenerative diseases, including Parkinson's disease, Alzheimer's disease and amyotrophic lateral sclerosis. However, details about the role of endoplasmic reticulum-mitochondria contact sites in neurodegenerative diseases remain unknown. In Parkinson's disease, interactions between α-synuclein in the contact sites and components of tether complexes that connect organelles can lead to various dysfunctions, especially with regards to calcium homeostasis. This review will summarize the main tether complexes present in endoplasmic reticulum-mitochondria contact sites, and their roles in calcium homeostasis and trafficking. We will discuss the impact of α-synuclein accumulation, its interaction with tethering complex components and the implications in Parkinson's disease pathology.